Business ethics for better behavior - Brennan, Jason 1979-; English, William; Hasnas, John; Jaworski, Peter (Findaway World, 2022)
A clear and concise roadmap for ethical business behavior using commonsense moral principlesBusiness Ethics for Better Behavior concisely answers the three most pressing ethical questions business professionals face: What makes business practices right or wrong?; Why do normal, decent businesspeople of good will sometimes do the wrong thing?; and How can we use the answer to these questions to get ourselves, our coworkers, our bosses, and our employees to behave better?Bad behavior in business rarely results from bad will. Most people mean well much of the time. But most of us are vulnerable. We all fall into moral traps, usually without even noticing.Business Ethics for Better Behavior teaches business professionals, students, and other listeners how to become aware of those traps, how to avoid them, and how to dig their way out if they fall in. It integrates the best work in psychology, economics, management theory, and normative philosophy into a simple action plan for ensuring the best ethical performance at all levels of business practice. This is a book anyone in business, from an entry-level employee to CEO, can use.
Online resource ; title from cover image (EBSCO, viewed April 8, 2022)
Keywords: Business ethics; Morale des affaires; Downloadable audio books; Audiobooks; Livres audio